2011
DOI: 10.4103/0971-4065.78062
|View full text |Cite
|
Sign up to set email alerts
|

Role of free radicals and antioxidant status in childhood nephrotic syndrome

Abstract: Nephrotic syndrome (NS) is characterized by heavy proteinuria and hypoalbuminuria. Reactive oxygen species (ROS) seem to play an important role in the etiopathogenesis of proteinuria in NS. This study aims to evaluate the potential role of reactive oxygen species in pathogenesis of NS by estimating the levels of oxidants and antioxidants in children with NS. Thirty patients of NS and thirty age, sex-matched healthy subjects, were selected for the study. As compared to healthy controls, the levels of serum lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…MDA is an important end-product generated by lipid peroxidation and has been used to demonstrate increased oxidative stress during chronic kidney disease [ 45 ]. In our study, rats in ADR-treated group presented with high level of plasma MDA which indicated an increased lipid peroxide concentration [ 46 , 47 ]. ZWT decreased plasma MDA and inhibited the lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…MDA is an important end-product generated by lipid peroxidation and has been used to demonstrate increased oxidative stress during chronic kidney disease [ 45 ]. In our study, rats in ADR-treated group presented with high level of plasma MDA which indicated an increased lipid peroxide concentration [ 46 , 47 ]. ZWT decreased plasma MDA and inhibited the lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress plays an important role in the pathogenesis of several diseases, including renal diseases, and may be associated with the pathogenesis of proteinuria in NS patients [4]. Reactive oxygen species (ROS) play an important role in the development of progressive renal damage [5].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies [9][10][11][12][13][14][15][16] have showed the alterations of these parameters in the INS subjects. However, the relative small number of participants limited the statistical power, and some of the results were in conflict.…”
Section: Introductionmentioning
confidence: 99%